A chemiluminescence method for the determination of verapamil hydrochloride in pharmaceutical and environmental samples based on an Fe3O4 nanoparticles enhanced NaHCO3–H2O2 system. Issue 47 (27th November 2017) - Iranifam, Mortaza; Hendekhale, Nasim Rahmati
Abstract : In this work, an Fe3 O4 nanoparticles (NPs)-enhanced chemiluminescence (CL) method was developed for the determination of verapamil hydrochloride (VRP). Abstract : In this work, an Fe3 O4 nanoparticles (NPs)-enhanced chemiluminescence (CL) method was developed for the determination of verapamil hydrochloride (VRP). To this aim, a quick precipitation method was employed to synthesize Fe3 O4 NPs. The synthesised Fe3 O4 NPs were then characterized by using techniques including Fourier Transform Infrared (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM). It was found that the Fe3 O4 NPs were able to enhance the NaHCO3 –H2 O2 CL reaction. In addition, it was shown that VRP had an inhibitory effect on the Fe3 O4 NPs–NaHCO3 –H2 O2 system in such a way that the CL intensity was inversely proportional to the concentration of VRP. These findings were used for the establishment of a new, green, simple and sensitive CL analytical method for VRP with a linear dynamic range of 5.0 × 10 −6 to 1.0 × 10 −3 mol L −1, a correlation coefficient ( r 2 ) of 0.99 and a limit of detection of 2.8 × 10 −6 mol L −1 . The CL method was successfully used for the determination of VRP in pharmaceutical formulations.